The Extent of Manure Removal from Storages and Its Impact on Gaseous Emissions. Issue 6 (1st November 2016) - Ngwabie, N. M.; Gordon, R. J.; VanderZaag, A.; Dunfield, K.; Sissoko, A.; Wagner‐Riddle, C.
Abstract : Manure remaining in storage due to incomplete removal is a source of microbial inoculum that may affect methane (CH4 ), nitrous oxide (N2 O), and ammonia (NH3 ) emissions during subsequent storage. Manure removal was studied by loading fresh manure into outdoor concrete tanks (10.6 m 3 ) that contained previously stored manure (inoculum) at six levels (0, 5, 10, 15, 20, and 25%, with 0% representing an empty tank). Emissions were continuously measured for 6‐mo storage periods (warm and cold seasons) using flow‐through chambers. Fluxes during the warm season (average manure temperature at 80 cm depth, T m = 17°C) were 25 times higher for CH4, 20 times higher for N2 O, and 2.9 times higher for NH3 compared with the cold season ( T m = 4°C). Cumulative CH4 emissions increased linearly with the level of added inoculum in the cold season ( r 2 = 0.98). A similar linear increase was observed in the warm season from 0 to 20% inoculum ( r 2 = 0.91), after which a decrease in emissions was observed at 25%. Reducing inoculum from 15 to 5% reduced CH4 emissions by 26% in the warm season and 45% in the cold season. There was no clear effect of inoculum on N2 O and NH3 emissions, suggesting that complete manure storage emptying does not alter their emissions. Core Ideas: Manure in storage from incomplete removal is a source of microbial inoculum affecting CH4 emissions. Cumulative CH4 emissions increased linearly with the level of added inoculum in the cold season. Cumulative CH4 emissions increased linearly from 0 to 20% inoculum in the warm season. Reducing inoculum from 15 to 5% reduced CH4 emissions in warm season by 26% and cold season by 45%.